Desalination of Seawater. Osmotic Process for “Blue Energy” and Estimation for Desalination - Ignatov, I.; Gluhchev, G.; Ignatov, A.I. (Publishing house "Academperiodika", 2024)
Seawater, a vast resource, holds fresh water that is increasingly crucial in industrially developed countries. The demand for freshwater for domestic use, agriculture, and industry in these nations far surpasses the available supplies, leading to freshwater scarcity. Your invaluable work in water resource management and environmental science, which is pivotal in addressing this issue, is greatly appreciated. This issue is not limited to specific countries in places like Israel and Kuwait, where the level of precipitation is very low, and freshwater reserves do not meet the increasing needs due to the modernization of the economy and population growth. This global relevance underscores the importance of desalination technologies as a potential solution. As we explore the potential of desalination technologies, we are presented with a promising solution to water scarcity- the vast seas and oceans as alternative water sources. This potential is particularly significant in your field of research and expertise, underscoring the relevance of this paper to your work. The countries with the cleanest drinking water usually have large freshwater reserves in lakes, rivers, underground waters, and glaciers, providing a reassuring buffer against water scarcity. Brazil, for instance, benefits from abundant freshwater from the Amazon River and its extensive basin system. Canada boasts numerous lakes and river systems. The United States include large freshwater reserves in the Great Lakes, numerous rivers, and groundwater. Colombia has large freshwater resources, primarily due to numerous rivers and groundwater. Chile is rich in glacier water, further enhancing its water security. This diverse range of water resources underscores the need for desalination technologies to supplement these sources. In Europe, the Scandinavian countries Norway and Sweden have natural resources for clean drinking water from mountain rivers and lakes. Denmark is flat, but like the other Scandinavian countries, it maintains strict environmental ...